Web-Based Student Violation Management with Real-Time Notifications Transforms School Discipline: Manajemen Pelanggaran Siswa Berbasis Web dengan Notifikasi Waktu Nyata Mengubah Disiplin Sekolah - Krisfianto, Moh Ifan; Indahyanti, Uce (Universitas Muhammadiyah Sidoarjo, 2024)
General background: The digital age has significantly impacted education, posing challenges in managing student behavior and addressing rule violations, necessitating more efficient solutions. Specific background: Educational institutions are exploring the use of web-based systems with real-time notifications to improve efficiency in recording and communicating student violations. Knowledge gap: Despite the advancements in technology, many schools have yet to fully adopt integrated digital systems for managing student violations, and the effectiveness of real-time notification systems has not been fully explored. Aims: This study aims to design and develop a web-based application for managing student violations, integrated with WhatsApp notifications, to improve efficiency, accuracy, and communication between schools and parents. Results: Using the Extreme Programming (XP) methodology, the system was developed iteratively, allowing for rapid adjustments based on user feedback. The system successfully reduced errors in violation recording and accelerated communication with parents, facilitating faster responses to student misconduct. Novelty: The web-based violation management system incorporates real-time WhatsApp notifications, offering a more efficient and trustworthy communication channel between schools and parents. Implications: The system enhances both the management of student behavior and the engagement of parents, and it serves as an innovative model for other educational institutions to adopt for more effective administration and improved educational outcomes. Highlights: Efficiency: Reduces errors in managing student violations. Communication: Enhances parent-school connection via real-time WhatsApp notifications. Adaptability: XP methodology supports rapid adjustments and iterative development. Keywords: Web-based system, student violations, real-time notifications, WhatsApp integration, Extreme Programming